Development of Standard Assessment for Understanding Green Chemistry Principles Based on Unity of Science - Atik Rahmawati; Sri Mulyanti; Khoirul Ummah (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2024)
Understanding green chemistry is a crucial aspect for chemistry teacher graduates, as it equips them with the knowledge and skills to promote sustainable practices, minimize environmental impact, and inspire the next generation of students to engage in eco-friendly scientific innovation. This research is dedicated to developing a standard assessment for understanding Green Chemistry based on the Unity of Science (UoS), which is grouped into three categories: reagents, reaction processes, and reaction products. The research uses a mixed methods design with a triangulation model. A significant part of the research process is the validation of the feasibility of the instrument developed, which was done by five chemical experts. The multi-rater responses obtained were then analyzed using the feasibility criteria of the processed Rasch results. In the trial process, 40 students from the Chemistry Education program were selected as research subjects. The results showed that the reliability of the questions was 0.87, with an item separation level of 2.54. This reliability value of 0.87 indicates that the developed questions are of excellent quality and can be used as a standard for measuring understanding of Green Chemistry based on Unity of Science.